2015
DOI: 10.1007/s11042-015-3104-5
|View full text |Cite
|
Sign up to set email alerts
|

Orientation judgment for abstract paintings

Abstract: Artists decide the orientation at which an abstract painting should be hung based on their ideas, but the correct orientation is not obvious to other viewers. Some studies have found that abstract paintings at the correct orientations generally get higher aesthetic ratings from viewers. This encourages us to deal with the problem of orientation judgment for abstract paintings through machine learning. First, we design a group of methods to extract features from paintings based on the theories in abstract art. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…For answering the first question, we inspected the order of pictures with respect to balance. Our impression was that perceived stability (Liu et al., 2017; van der Helm, 2015) might explain some of the variance. Therefore, in our second experiment, we asked our participants to assess the stability of the calligraphies.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…For answering the first question, we inspected the order of pictures with respect to balance. Our impression was that perceived stability (Liu et al., 2017; van der Helm, 2015) might explain some of the variance. Therefore, in our second experiment, we asked our participants to assess the stability of the calligraphies.…”
Section: Discussionmentioning
confidence: 91%
“…In this experiment, we collected ratings of stability (Liu et al., 2017; van der Helm, 2015) as well as of prototypicality (Rosch, 1975) for the Japanese calligraphies already used in our first experiment. Stability ratings were used to examine to what extent this dimension corresponds to the concept of perceptual balance for the calligraphies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanisms underlying orientation judgements are not fully understood. Some authors have suggested that the perception of orientation depends more on low-level stimulus properties than higher level object recognition and/or image interpretation ( Lindauer, 1987 ), prompting others to investigate the potential role of relatively simple cues, such as Fourier amplitude spectrum slope ( Mather, 2012 ), or image statistics based on explicit rules gathered from several art theories incorporated into a machine learning algorithm ( Liu et al., 2017 ) (see Elgammal et al., 2018 ; Rodriguez et al., 2018 for related applications).…”
Section: Introductionmentioning
confidence: 99%